The Trickle Algorithm: Issues and Solutions - Djamaa, Badis; Richardson, Mark A. (Cranfield University, 2015)
To manage the various multi-purpose Internet of Things applications brought about by low-power and lossy networks, efficient methods of network configuration and administration; firmware installation and updates; neighbourhood, route and resource discovery are required. These requirements can be reduced to a basic data consistency maintenance problem, making the Trickle algorithm a powerful candidate solution. Trickle is shaped by the so-called short-listen problem, hence the imposition of a listen-only period. Such a period allows Trickle to robustly address the short-listen problem at the expense of increased latency. In this report, we revisit the Trickle rules, the short-listen problem and interval-synchronisation, and hence introduce New-Trickle. New-Trickle is an optimisation to Trickle with virtually no extra cost in terms of communication overhead, computation demand and implementation effort, yet one that provides fast updates, yielding a propagation time more than 10 times faster than Trickle.